Design and the Evolving Tradition of Sanganer Hand Block Printing: Formation and Negotiation of Artisanal Knowledge and Identities Against the Backdrop of Intangible Cultural Heritage. (4th May 2017) - Greru, Chamithri; Kalkreuter, Britta
Abstract: Tradition has been described by heritage studies as a transformative process that is being enforced, reinvented, transformed, denied, or contested, with heritage seen as a construct of the past, present, and imagined futures. The role of craft and design interactions in safeguarding and rejuvenating cultural practices has yet to receive adequate attention against this theoretical backdrop. In order to discuss how design affects craft practices, we studied Sanganer hand block printing's development amidst increasing design influences in postindependence India. We especially consider the way in which artisanal identities and practice, or intangible cultural heritage, are formed and negotiated when engaged with specific design scenarios and actors; and by studying the varied attitudes and realities of contemporary Sanganer hand block printing from this interdisciplinary point of view, the paper offers new insights into a range of "modern, " "traditional, " and "heritage" craft realities.